Elevated body mass index and body fat percentage are associated with decreased physical fitness in soccer players aged 12-14 years - Nikolaidis, P. T. (Asian Journal of Sports Medicine, 2012)
Purpose: Adolescents are in increased risk for the development of obesity, while sport has been suggested as an effective means against adolescent obesity. The objectives of this study were to examine (a) the prevalence of overweightness/obesity, (b) the relationship between body mass index (BMI) and body fat percent (BF), and (c) the association between BMI, BF and physical fitness in adolescent soccer players.